O desempenho da performance financeira superior a partir da visão baseada em recursos: um estudo dos bancos brasileiros - Bellozupko Junior, Davi (2020)
The field of strategy is broad and constantly expanding, so there are many theories used to understand the influence and the relationship of strategy to achieve superior competitive advantage. One of the theories that is recognized in the literature and demonstrates the idea of competitive advantage is the resource-based view (RBV). Based on the principle that its use can generate competitive advantage, it is necessary to evaluate the performance of organizations. Competitive advantage is a topic that still arouses much interest in the academic and business world. However, analyzing and demonstrating what drives a company to develop a competitive advantage over its competitors is not a simple task. The objective of this research is to measure how the internal resources and capacities of Brazilian financial institutions (IFBs) can affect their financial performance, respectively between the years 2014 and 2018. This dissertation sought theoretical references that could support the research with emphasis on the RBV theory. Under this argument, this study develops a theoretical review of the RBV and debates with other related theories, in order to present constructs that could provide theoretical and scientific support to this research. In methodological terms, this quantitative work was carried out through the collection of secondary data from the 22 largest Brazilian banks and the statistical analysis of the data took place using the panel data regression method using the Gretl statistical tool, being tested three main hypotheses, each hypothesis with two study models being one for the dependent variable ROA and another dependent variable ROE, totaling six models of analysis and two models for each hypothesis. These tests and their analysis brought several reflections and findings about the relationship between internal capabilities and resource management and the superior financial performance of IFBs. As for the results obtained from the tests carried out, the hypotheses presented showed the importance of resource-based management to obtain a superior financial performance. With this, the study opens a discussion about the role of organizational managers and their importance in the sense of observing each evidence that can be related to the internal capacities of an organization and its use of resources, or capacity to manage these resources with a view to obtaining superior financial performance over competitors in the operating segment. The practical results of this research can be used in academic studies, by banks and as a basis for future studies on the subject. On the theoretical aspect, this research aimed to contribute to the field of organizational studies in the sense of expanding the debate on sustainable competitive advantages.